BESAR PENGARUH STRATEGI-STRATEGI PEMBELAJARAN DALAM PENDIDIKAN FISIKA: SEBUAH TINJAUAN META-ANALISIS BERDASARKAN JENIS STRATEGI DAN JENJANG PENDIDIKAN SISWA - Miriam, Sarah (Vidya Karya Jurnal Kependidikan, 2015)
This research aimed at describing the effect sizes (ESs) of instructional strategies on student achievement in physics viewed from kinds of instructional strategies and levels of education. The phases in this research included: study acquisition, study selection, and conducting the analyses. This research included 23 primary studies that have generated 29 sub-studies as the research subjects. The analysis revealed: (a) the mean of ESs of the eight kinds of instructional strategies were in big category, the five kinds were in moderate category, and the two kinds were in small category, (b) the mean of ESs at levels of junior high school and university were in big category, while at senior high school the mean of ES was in moderate category. The results from this meta-analysis support the effectiveness of non-conventional instructional strategies in physics and have generated a big impact on grand mean of the ES that was found to be 1.020.